Design and simulation of a two- or four-stroke free-piston engine generator for range extender applications. (1st March 2016) - Jia, Boru; Smallbone, Andrew; Zuo, Zhengxing; Feng, Huihua; Roskilly, Anthony Paul
Highlights: A FPE model operated in two thermodynamic cycles is presented. The engine performance for both gas exchange cycles are described. Power distribution with different operation parameters are provided. Advantages and disadvantages for the two thermodynamic cycles are summarised. Abstract: Free-piston engines (FPEs) are known to have a greater thermal efficiency (40–50%) than an equivalent and more conventional four-stroke reciprocating engines (30–40%). Modern FPEs are proposed for the generation of electric and hydraulic power, with a potential application in hybrid electric vehicles. The numerous FPE configurations considered to date have almost exclusively operated using a two-stroke thermodynamic cycle to improve the thermal efficiency, however it is well known that the application of two-stoke cycles can be limited by noise and exhaust gas emissions constraints. In this article, a numerical model is used to investigate the techno-feasibility of operating Newcastle University's FPE prototype using a two- or four-stroke thermodynamic cycle. If operated as a four-stroke cycle, the linear generator must be used as both a motor and a generator resulting in a more irregular piston motion compared to corresponding operating in a two-stroke cycle. In four-stroke cycles, almost half the indicated power is consumed in overcoming the pumping losses of the motoring process. Whilst the heat release process is appears to be closer to a constant volume process when operated on two-stroke engine cycle, the peak cylinder pressure and compression ratio proved lower. In addition, a narrower power range is reported for a four-stroke cycle despite a corresponding higher thermal efficiency.